2020
DOI: 10.1111/gcb.14960
|View full text |Cite
|
Sign up to set email alerts
|

Fluvial CO2 and CH4 patterns across wildfire‐disturbed ecozones of subarctic Canada: Current status and implications for future change

Abstract: Despite occupying a small fraction of the landscape, fluvial networks are disproportionately large emitters of CO2 and CH4, with the potential to offset terrestrial carbon sinks. Yet the extent of this offset remains uncertain, because current estimates of fluvial emissions often do not integrate beyond individual river reaches and over the entire fluvial network in complex landscapes. Here we studied broad patterns of concentrations and isotopic signatures of CO2 and CH4 in 50 streams in the western boreal bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 122 publications
(217 reference statements)
0
24
0
2
Order By: Relevance
“…7av). Further, immediately downstream of the RTS FM2 inflow to Dempster Creek, the decrease in CO 2 and shift in δ 13 C-CO 2 away from a biotic source suggest that CO 2 degassing to the atmosphere was more prominent than respiration of permafrost DOC (Doctor et al, 2008;Drake et al, 2018b;Kendall et al, 2014). Thus, immediately downstream of RTSs, microbial respiration of permafrost DOC does not appear to generate substantial CO 2 .…”
Section: Integration Of Rts Effects On Carbon Cycling Across Watershementioning
confidence: 97%
See 2 more Smart Citations
“…7av). Further, immediately downstream of the RTS FM2 inflow to Dempster Creek, the decrease in CO 2 and shift in δ 13 C-CO 2 away from a biotic source suggest that CO 2 degassing to the atmosphere was more prominent than respiration of permafrost DOC (Doctor et al, 2008;Drake et al, 2018b;Kendall et al, 2014). Thus, immediately downstream of RTSs, microbial respiration of permafrost DOC does not appear to generate substantial CO 2 .…”
Section: Integration Of Rts Effects On Carbon Cycling Across Watershementioning
confidence: 97%
“…While respiration likely produced some CO 2 in RTS FM2 runoff (Littlefair et al, 2017), observed δ 13 C-CO 2 (−11 ‰) more strongly reflected H 2 SO 4 weathering of regional carbonate bedrock (−0.7 ‰ to −5.6 ‰; Hitchon and Krouse, 1972) when accounting for isotopic fractionation of ∼ 8 ‰ between carbonate and CO 2 at the temperature of FM2 runoff (18 • C; Clark and Fritz, 1997). Along the lower reach of the FM2 runoff transect, the increase in δ 13 C-CO 2 aligned with the preferential loss of 12 C in the CO 2 phase via DIC fractionation and degassing (Doctor et al, 2008;Drake et al, 2018b;Kendall et al, 2014). 13 C enrichment of the CO 2 pool by methanogenesis (Campeau et al, 2018), photosynthesis (Descolas-Gros and Fontungne, 1990), and/or calcite precipitation (Turner, 1982) was unlikely as CH 4 in FM2 runoff was relatively low (pCH 4 = 3.6 ± 1.9 µatm, mean ± SD, n = 6), the high turbidity of FM2 runoff likely inhibited photosynthesis (Levenstein et al, 2018), and calcite was below saturation (SI = −0.79).…”
Section: Rapid Carbon Cycling In Fluvial Network Headwatersmentioning
confidence: 98%
See 1 more Smart Citation
“…NEP savanna and NEP wetland are the annual net terrestrial C productivity for the savanna and wetland components, respectively, and NEP is the area-weighted average for the whole catchment. Percentages in parentheses for each landscape component at the top of the diagram correspond to area weightings [Colour figure can be viewed at wileyonlinelibrary.com] et al, Horgby et al, 2019;Hutchins, Tank, et al, 2020). (Iversen et al, 2019).…”
Section: Uncertainties On Aquatic C Export Estimatesmentioning
confidence: 99%
“…By combining measurements of 14 C of dissolved organic carbon and CO 2 released from northern permafrost peatlands to 13 C-CO 2 analyses, D. Olefeldt and his group were able to co-currently determine the age and sources of CO 2 to streams and to differentiate between CO 2 released from weathering vs. soil organic matter degradation (Burd et al 2018;Estop-Aragonés et al 2018). In addition, 13 C-CH 4 chamber measurements were used to assess whether methane was produced via acetoclastic or hydrogenotrophic pathways in wetland soils of different permafrost conditions and from thermokarst ponds in peatlands (Hutchins et al 2020). Lastly, 13 Clabelled glucose was added to peat during anaerobic incubations to test hypotheses of primingagain to study whether peat following permafrost thaw is vulnerable to rapid decomposition (unpublished results).…”
Section: Carbon Isotopesmentioning
confidence: 99%